PROTEINS OF PAROTOID GLAND SECRETIONS FROM TOADS OF THE GENUS BUFO - Perry, David (Contemporary Herpetology, 2000)
Freeze-dried parotoid gland secretions from toads of the genus Bufo contained large proportions of protein (25-35% by weight). SDS-PAGE suggested that secretions from several species of Bufo contained mixtures of proteins in the relative molecular mass range of approximately 12 - 200 kDa, which exhibited markedly different banding patterns from species to species. These proteins were presumably not discovered before because the previous extraction procedures used with these secretions were designed to examine low molecular mass compounds and would denature the proteins. SDS-PAGE of secretions from B. mauritanicus and B. calamita are shown here. The N-terminal amino acid sequence of one of the bands (approx. 58 kDa) of B. mauritanicus was found to be LPIPAFPGLDHGF and of a B. calamita band (30.5 kDa) was VQVFGLQKEA. No significant similarities to these two sequences and to three separate but partial N-terminal sequences obtained from these species were found in genetic databases.